Larger right atrium than left atrium is associated with all‐cause mortality in elderly patients with heart failure. Issue 5 (14th March 2017) - Almodares, Qays; Wallentin Guron, Cecilia; Thurin, Anders; Fu, Michael; Kontogeorgos, Silvana; Thunstrom, Erik; Johansson, Magnus C.
Abstract : Background: While left atrial (LA) enlargement is known as an early sign of left heart disease with prognostic implications in heart failure (HF), the importance of right atrial (RA) enlargement is less well studied, and the prognostic implications of interatrial size comparison are insufficiently understood. The aim of this study was to test the hypothesis that RA area larger than LA area in apical four‐chamber view is associated with all‐cause mortality in elderly patients with HF independent of left ventricular ejection fraction (LVEF). Methods: Retrospectively, 289 patients above 65 years hospitalized for HF between April 2007 and April 2008, and who underwent an echocardiogram, were enrolled. All‐cause mortality was registered during a follow‐up of at least 56 months. Baseline parameters measured were RA area, LA area, LA volume, LVEF, left ventricular mass (LVM), tissue Doppler systolic velocity of right ventricular free wall (SmRV), presence of severe tricuspid regurgitation (TR), tricuspid gradient, central venous pressure, systolic pulmonary artery pressure, as well as some parameters of diastolic function. Results: In univariate analysis RA larger than LA was associated with all‐cause mortality (hazard ratio [HR] of 1.88, P <.001). The relation of RA larger than LA to all‐cause mortality remained even after adjusting for age, heart rate, LVEF, atrial fibrillation, percutaneous coronary intervention, LVM index, LA volume index, SmRV, and the presence of severe TR (HR: 1.79, P =.04). Conclusion: RA larger than LA, independently of LVEF, is associated with all‐cause mortality in elderly patients hospitalized due to HF.